RESPONSE OF SEED GERMINATION AND GROWTH OF Nepenthes gymnamphora Nees IN VITRO TO THE CONCENTRATION OF MS MINERAL SALT, PEPTONE AND THIDIAZURON - Fella Suffah Meinaswati; Nintya Setiari; Yulita Nurchayati; Sri Widodo Agung Suedy (Balai Bioteknologi, Badan Pengkajian dan Penerapan Teknologi (BPPT), 2022)
Nepenthes gymnamphora Nees is a Java's rare endemic species. Ex-situ conservation of this endangered species can be done through in vitro culture technique. The aims of this study were to determine (1) the mineral salt concentration of MS basal media and addition of peptone (P) on N. gymnamphora seed germination and seedling emergence and (2) the effects of TDZ in ½MS medium on seedling growth. Seeds were surface sterilized and cultured on four media formulations (½MS, MS, ½MS+P, MS+P) for 8 weeks. In the second experiment, ten-week-old seedlings, 0,25 cm in length were cultured on ½MS supplemented with 0, 0,5, 1,0, or 1,5 mg/L TDZ. Seedling growth was recorded at 8 weeks of culture. Results of this experiment showed that ½MS was the best medium for N. gymnamphora seed germination as indicated by the highest percentage of germination, the tallest seedling, and the fastest seedling emergence. Moreover, the best growth of N. gymnamphora was found on ½MS without TDZ. Nepenthes gymnamphora Nees. merupakan spesies endemik Pulau Jawa yang tergolong langka, sehingga perlu upaya konservasi. Konservasi ex situ spesies ini dapat dilakukan dengan teknik kultur jaringan. Penelitian ini bertujuan untuk mengetahui konsentrasi garam mineral media MS dan pepton yang dapat mendukung perkecambahan biji dan menentukan konsentrasi TDZ untuk pertumbuhan kecambah N. gymnamphora in vitro. Pada percobaan I, biji N. gymnamphora disterilisasi dan ditabur di 4 kombinasi media, yaitu MS, ½MS, dengan dan tanpa penambahan 2g/L pepton. Pada percobaan II, kecambah berukuran ± 0,25 cm dengan penambahan beberapa konsentrasi TDZ (0; 0,5; 1; 1,5 ppm) pada media ½MS. Hasil penelitian menunjukkan bahwa media ½MS menghasilkan persentase perkecambahan biji tertinggi (56%) dengan tinggi kecambah kecambah terbaik. Media ½MS tanpa TDZ menghasilkan pertumbuhan kecambah terbaik yang ditunjukkan oleh waktu tercepat munculnya daun, Media ½MS merupakan konsentrasi garam mineral terbaik untuk perkecambahan biji N. gymnamphora, tanpa TDZ.